Increasing Production of Chilli (Capsicum annuum L.) through Foliar Fertilizer Application - Sugiyanta Sugiyanta; Juang Gema Kartika (Department of Agronomy and Horticulture, IPB University, 2018)
Chili is one of the most important spices in Indonesia; the demand for chili is increasing along with the growth of the population. Chilli is generally grown under intensive culture which includes addition of fertilizers to improve crop growth and increase crop productivity. A study was conducted to examine seven different rates of an inorganic foliar fertilizer HF at 0.5, 0.75, 1, 1.25 and 1.5 of the recommended rate, with no foliar fertilizer and a standard foliar fertilizer GD as control. The results showed that spraying foliar fertilizer HF generally improved the growth and yield of chilli compared to without fertilizer. Plant height, number of branches and number of fruits per plant, weight per fruit, weight per 10 fruits, yield per plant, yield per plot, and yield per ha of chilli treated with inorganic fertilizers was significantly higher than the without foliar fertilizer. Foliar fertilizer HF at 0.5 of the recommendation rate, or 1 kg.ha-1 foliar fertilizer applied at 4, 6, 8, 10, and 12 week after planting in addition to the basic fertilizers of 400 kg.ha-1 of urea, 200 kg.ha-1 of SP-36, 250 kg.ha-1 of KCl applied to the soil, was effective to obtain the maximum chilli fruit yield.